A STUDY ON REGISTER USED AMONG SOLDIERS OF KORAMIL 0809/04 GAMPENGREJO KEDIRI IN INFORMAL CONVERSATION - ULANDASARI, WURI KURNIA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords : Register, Soldier, Kediri, Koramil, Informal Conversation Nowadays, people as social creature must be able to adapt with the society.One of the ways to adapt in the society is by using language as communicationdevice. This will make the society builds a group of people according to thereligion, social class, similarity and so on. In certain group, people need their own language, then they make some technical terms which are only understood by the group. As the result, this phenomenon makes a variation in a language and one of the variation is register. In this study, the writer learns about the use of register among soldiers in informal conversation of KORAMIL 0809/04 Gampengrejo Kediri. This study examines (1) the kinds of register used among soldiers in informal conversation; (2) the meaning of each register which is used by soldiers in informal conversation.In this research, the writer used qualitative method with homogeneous samples that are chosen from the soldiers of KORAMIL 0809/04 Gampengrejo Kediri who have more knowledge and experience as a soldier. In this study, to acquire the data, the writer interviewed the samples with different topics. This study describes the use of register which has appropriate meaning related to the topic used by the soldiers of KORAMIL 0809/04 Gampengrejo Kediri.The writer found eleven (11) registers which are used by soldiers in theconversations. The register has its own meaning which is different from other register. This shows that the similarity of using the register is influenced by theknowledge and experience of soldiers when they are on duty.The writer suggests to the next researchers to do the research about the kinds of register which are used by policeman when they do the conversation with their leader, when they involve in formal conversation or when they are on duty in war. Future researchers can proceed making research about registers in different field such as the Police Department.